2016
DOI: 10.1177/1082013216658580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sous vide processing on physicochemical, ultrastructural, microbial and sensory changes in vacuum packaged chicken sausages

Abstract: The processing of sous vide chicken sausages was optimized under vacuum packaging condition and cooking at 100 ℃ for 30 min (SV30), 60 min (SV60) and 120 min (SV120) and compared with aerobically cooked control at 100 ℃ for 30 min. Sous vide processing of chicken sausages (SV30) produced higher (p < 0.05) cooking yield, Hunterlab a* values and sensory attributes without affecting proximate composition and shear force values relative to control. The sodium dodecyl sulphate-polyacrylamide gel electrophoresis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
15
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
10
15
1
2
Order By: Relevance
“…For this reason, it is considered that food safety will be enhanced by applying sous vide after cooking. In line with this decision, Naveeba et al () reported that coliforms were not observed in SV cooked (at 100 °C for 30 min) chicken sausages during 120 days of storage at 4 °C.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…For this reason, it is considered that food safety will be enhanced by applying sous vide after cooking. In line with this decision, Naveeba et al () reported that coliforms were not observed in SV cooked (at 100 °C for 30 min) chicken sausages during 120 days of storage at 4 °C.…”
Section: Resultsmentioning
confidence: 87%
“…Because the packing was a recently applied trend for döner kebabs, there was no previous literature of the results which demonstrated the shelf life and microbial growth in packed döner kebabs during storage; so they could not be compared. But similarly, corresponding with the application of SV technology, Naveeba et al () stated that TMAB counts of SV applied (100 °C 30 min) chicken sausages were below 6 log cfu/g after the 120 day storage at 4 °C while its level reached to 9 log cfu/g in traditionally produced chicken sausages after 20 days of storage. Besides, Nyati () reported that the application of SV technology at 70 °C for 2 min reduced the TMAB count of turkey meats from 3 log cfu/g to 1 log cfu/g and pointed out that TMAB counts were not below 3 log cfu/g during 5 week storage at 3 °C.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Sous-vide cooking is used in the processing food, as well as in catering and food services, to improve the properties and maintain nutrients in sheep meat (Roldàn et al, 2013) chicken sausage (Naveena et al, 2017) carrots and brussels sprouts (Chiavaro et al, 2012) and fish curry (Shakila et al, 2012). Sous-vide cooking involves vacuum packing in pouches and then cooking for protracted periods (Baldwin, 2012), which can result in foods having less change in color and improved texture (Creed, 1995).…”
Section: Introductionmentioning
confidence: 99%